Surveillance of surgical-site infections and antimicrobial resistance patterns in a tertiary hospital in Alexandria, Egypt - May Raouf; Thoraya Ghazal; Mohamed Kassem; Abdelfattah Agamya; Amira Amer (Journal of Infection in Developing Countries)
Introduction: Surveillance and antimicrobial resistance (AMR) monitoring are fundamental to Health care associated infections control. Limited data are available from developing countries for both. This study aimed to evaluate incidence and risk factors of surgical site infections (SSIs), etiological pathogens and AMR patterns identification.